Brill's companion to Herodotus - Bakker, Egbert J.; Wees, Hans van.; Jong, Irene J. F. de. (Brill's Companions to Classical Studies., 2002)
Herodotus' Histories can be read in many ways. Their literary qualities, never in dispute, can be more fully appreciated in the light of recent developments in the study of pragmatics, narratology, and orality. Their intellectual status has been radically reassessed: no longer regarded as naïve and 'archaic', the Histories are now seen as very much a product of the intellectual climate of their own day - not only subject to contemporary literary, religious, moral and social influences, but actively contributing to the great debates of their time. Their reliability as historical and ethnographic accounts, a matter of controversy even in antiquity, is being debated with renewed vigour and increasing sophistication. This Companion offers an up-to-date and in-depth overview of all these current approaches to Herodotus' remarkable work.